ANALYSIS OF PHYSICS LEARNING MATTER INTEGRATED DISASTER IN WEST SUMATERA - Muhammad Arif; Dina Syaflita (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
West Sumatera is a disaster prone area, especially disasters such as earthquakes, landslides, floods, tsunamis, and volcanoes. The high potential of natural disasters has consequences for the importance of disaster mitigation efforts. School is an effective tool in shaping of mindset and behavior of students. One effort that can be done is integrate the topic of natural disaster into learning, especially physics learning. Integrating physical matter in learning requires material analysis aimed at making disaster topics integrated in accordance with learning topic. The type of this research is descriptive research. The results of the research indicate that an analysis of the relevance of learning material to the topic of integrated disasters needs to be done so that the integration between teaching material and the topic of disasters is carried out in harmony. Almost all physics learning material can be integrated with the topic of disasters that often hit the West Sumatra region. The classification of material on the topic of integrated disasters is classified into fact and metacognitive material.